Comparison of Clinical Effectiveness and Tolerability of Single versus Split Methotrexate Doses as Initial Therapy in Rheumatoid Arthritis (Journal of Fatima Jinnah Medical University, 2026)
Background: Methotrexate is a first-line disease-modifying drug for rheumatoid arthritis, and is conventionally administered as a single weekly oral dose. In clinical practice, the weekly dose is sometimes split over 24 hours to reduce gastrointestinal adverse effects, although supporting evidence remains limited. This study aimed to compare the safety and efficacy of a single-dose versus a split-dose of oral methotrexate.Methods: This open-label interventional study was conducted at the Department of Rheumatology, Sir Ganga Ram Hospital, Lahore, Pakistan, between January and August 2025. A total of 56 patients aged 15-70 years fulfilling the ACR/EULAR-2010 criteria were enrolled. Patients with serious comorbidities, a prior biologic or recent conventional DMARD therapy, or pregnancy and lactation were excluded. Patients were allocated using systematic allocation (odd-even method) to receive either a single weekly oral dose or a split 24-hour oral dose of methotrexate. Methotrexate was initiated at 10 mg/week and increased to 25 mg/week according to response and tolerability. All patients received folic acid supplementation and tapering of low-dose prednisolone. Patients were followed for 24 weeks. Disease activity was measured using the Clinical Disease Activity Index (CDAI). Remission (CDAI ≤ 2.8) was the primary effectiveness endpoint, and methotrexate-related adverse effects were the primary safety outcome. The chi-square test was used to analyze the data, and a p-value
Keywords: Rheumatoid Arthritis; Methotrexate; Split Doing; Clinical Efficacy; Adverse Effects